Pembelajaran Jelajah Alam Sekitar (JAS) Berbasis Masalah Banjir Pada Materi Pokok Mitigasi Bencana Alam - Firnanda, Sa'dan; Santoso, Apik Budi (Edu Geography, 2019)
The purpose of this research is to find out: 1) The learning preparation about natural cruising around (JAS) method based on the material of flooding problem on natural disaster mitigation, include the natural cruising around RPP of natural disaster mitigation material 2) The implementation of natural cruising around (JAS) based on the material of flooding problem on the natural disaster mitigation include the activity of teacher and student activity, 3) The natural cruising around learning evaluation based on the material issues of the natural disaster mitigation include the results of the study of knowledge, study attitude result and study skills. The technique of collecting data are test, observation, question form, documentation, and interviews. The analytical techniques using descriptive precentage. The result of this reasearch showed that 1) The learning preparation is JAS RPP device of natural disaster mitigation material entered criteria very well with the percentage reached 91,7%, 2) The student activity in learning reached 85% and The tecaher activity reached 83,13% so, the criteria is very well 3) the results of study knowledge of students who complete test reached 77%, the results of the study skills is well with the average result of 81,25%. Tujuan Penelitian ini yaitu untuk mengetahui: 1) Perencanaan pembelajaran Jelajah Alam Sekitar (JAS) berbasis masalah banjir pada materi mitigasi bencana alam meliputi perangkat RPP Jelajah Alam Sekitar (JAS) materi Mitigasi Bencana Alam, 2) Pelaksanaan pembelajaran Jelajah Alam Sekitar (JAS) berbasis masalah banjir pada materi mitigasi bencana alam meliputi aktivitas guru dan aktivitas siswa, 3) Evaluasi pembelajaran Jelajah Alam Sekitar (JAS) berbasis masalah pada materi mitigasi bencana alam meliputi hasil belajar pengetahuan, hasil belajar sikap dan hasil belajar ketrampilan. Teknik analisis data menggunakan deskriptif persentase. Hasil penelitian menunjukan bahwa 1) persiapan pembelajaran yaitu perangkat RPP JAS materi Mitigasi Bencana Alam masuk kriteria sangat baik dengan persentase mencapai 91,7%, 2) Aktivitas siswa dalam pembelajaran yaitu 85% dan aktivitas guru mencapai 83,13% sehingga masuk kriteria sangat baik, 3) hasil belajar pengethauan dari 26 siswa memliki nilai rata-rata sebesar 82 dengan KKM yang diterapkan di sekolah sebesar 80, siswa yang mendapat nilai tuntas sebanyak 20 atau 77% sedangkan siswa yang belum tuntas sebanyak 6 atau 23%, sehingga dapat dikatakan hasil belajar pengetahuan siswa sebagian besar sudah tuntas.